(untitled) (International Journal of Research In Phytochemical And Pharmacological Sciences, 2018)
St John’s wort (also known as hypericum, millepertuis) is Hypericum perforatum L., Hypericaceae, an herbaceous perennial plant native to Europe and Asia, and which has been introduced into the United States where it has naturalized (38). The chemical composition of St. John’s wort has been well-studied. Documented pharmacological activities, including antidepressant, antiviral, and antibacterial effects, provide supporting evidence for several of the traditional uses stated for St John’s wort. Many pharmacological activities appear to be attributable to hypericin and to the flavanoid constituents; hypericin is also reported to be responsible for the photosensitive reactions that have been documented for St. John’s wort. This systematic review overviews the literature on the use of St. John’s Wort for chemistry, pharmacology and clinical properties.